Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Siswa Kelas VIII SMP Negeri 17 Medan - Latifa Hanum; Husnarika Febriani; Ulfayani Mayasari (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
The Disclosure Picking up learning model is a model for creating dynamic understudy learning techniques by self-revelation and self-examination, so that results will be gotten that will keep going quite a while in memory and are not handily forgotten by understudies. The reason for this exploration is to find out how results are impacted by utilizing the Disclosure Picking up learning model. Understudies in class VIII at SMP Negeri 17 Medan. The expression